A review of emergent vulnerabilities indices in the Alaska Arctic - Bushnell, E. J.; Miner, K.; Sousa, D.; Baskaran, L. (Frontiers in Environmental Science, 2025)
Human populations are increasingly impacted by climate change, especially in the Arctic, where Polar Amplification is accelerating impacts to more than four times the global average. The complex, interconnected risks that result need to be measured and tracked to characterize highly impacted areas. We reviewed a select cross-section of published vulnerability indices developed to characterize change in the Alaska Arctic. These pertain to permafrost thaw, water availability, animal habitat and migration, and anthropogenic development. While this cross-section offers a diversity of analysis, the next step would be to increase the accessibility of the indices to Arctic communities. Increasing availability of these tools will enable the incorporation and planning for these interconnected vulnerabilities.